The development of beech in monoculture and mixtures - Liziniewicz, Mateusz (2009)
The importance of producing good quality beech timber seems to increase even if there are periods with low demands for it. Due to relatively substantial amount of fertile abandoned agriculture soils in Southern Sweden possibilities to increase the area occupied by beech seems to be high. Former studies indicate the positive influence of shelter on a survival of seedlings and quality formation e.g. crookedness, forking. The aim of the study was to answer the question: if the shelterwood benefit to better quality of beech and which admixture species creates the most favourable conditions for beech regeneration? Furthermore, the goal was to study a possible hampering of the beech growth, due to the shelter. The thesis comprises two parts. In the first literature was reviewed, in the second field results were analyzed. Different beech traits were compared in mixed and open grown stands. The following beech traits were measured and judged on sample trees: diameter in breast height, diameter of the thickest branch, tree class, stem crookedness, quality of the stem, shape of the tree and occurrence of the spike knots. The statistical analyze was made by means of ANOVA planned comparisons. Every measured row was regarded as an independent observation. Contrast was made between three groups; NS (no shelter) - pure beech and mixture with alder (control plot), LS (low shelter) – mixtures with hornbeam, aspen and spruce, HS (high shelter) – mixtures with larch, birch, and hybrid aspen. The results showed that mixing beech with fast growing species has a positive influence on beech quality formation, especially shape of the tree and commercial quality. There was no significant decrease of diameter and volume growth of beech, due to the shelter. Finally the admixtures with fast growing species were regarded as the most favourable for artificial regeneration of beech.